2007
DOI: 10.1016/j.bbmt.2007.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Results of Unrelated Cord Blood Transplant in Fanconi Anemia Patients: Risk Factor Analysis for Engraftment and Survival

Abstract: We retrospectively analyzed results of unrelated cord blood transplantation (UCBT) in 93 Fanconi anemia (FA) patients. Median age at transplantation was 8.6 years (1-45). The units transplanted were HLA-A, -B, or -DRB1 identical in 12 cases, 1 HLA mismatch in 35 cases, and 2 or 3 HLA differences in 45 cases. The median number of nucleated cells (NC) and CD34+ cells infused of recipient weight was 4.9x10(7)/kg and 1.9x10(5)/kg, respectively. Participating centers selected the preparative regimen of their choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 42 publications
3
90
1
5
Order By: Relevance
“…2,[8][9][10]16,17 Children receiving a higher cell dose are less likely to experience fatal complications. 7,[15][16][17]46,47 In particular, the Minnesota group showed that recipients receiving a TNC dose before cryopreservation of o2.5 Â 10 7 /kg or CD34 þ infused cell dose of o1.7 Â 10 5 /kg had inferior neutrophil engraftment and slower recovery. 15 There were no differences in the median number of either TNCs or CD34 þ cells infused between our patients given MSCs and control groups of children receiving UCBT, with the majority of children receiving doses greater than the minimum threshold suggested by the Minnesota recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[8][9][10]16,17 Children receiving a higher cell dose are less likely to experience fatal complications. 7,[15][16][17]46,47 In particular, the Minnesota group showed that recipients receiving a TNC dose before cryopreservation of o2.5 Â 10 7 /kg or CD34 þ infused cell dose of o1.7 Â 10 5 /kg had inferior neutrophil engraftment and slower recovery. 15 There were no differences in the median number of either TNCs or CD34 þ cells infused between our patients given MSCs and control groups of children receiving UCBT, with the majority of children receiving doses greater than the minimum threshold suggested by the Minnesota recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Compared with BMT, UCBT offers the clinical advantages of absence of risks for the donor, reduced risk of transmitting infections, reduced incidence and severity of GVHD and, for transplants from UDs, rapid availability of cryopreserved cells, with the median time for a successful donor search being o1 month. 2,3,[8][9][10][11][12] Results of UCBT from either an HLA-compatible sibling or from a UD have been reported to be comparable with those obtained in children transplanted with BM cells.…”
Section: Introductionmentioning
confidence: 99%
“…There has repeatedly been an association between CMV positivity in the recipient and poorer transplant outcome, which may be due to the lack of prior exposure of CB cells to CMV. 15,48,49 ABO mismatches have been associated with delays in red cell and platelet transfusion independence. In a study, 95 adults who underwent unrelated CBT (27 ABO-identical, 29 minor, 21 major and 18 bidirectional ABO-incompatible recipients), Tomonari et al 50 reported that neutrophil and red cell engraftment did not differ but that the cumulative incidence of platelet engraftment in ABO-identical/minor ABO-incompatible recipients was higher than in major/ bidirectional ABO-incompatible recipients (Hazard ratio (HR) 1.88, P ¼ 0.013).…”
Section: Selection Of Unrelated Donor Cb For Transplantation: Other Fmentioning
confidence: 99%
“…It is in this population, where GVHD is not beneficial, one would expect to see the greatest impact of HLA matching. In a recent analysis of CBT for Fanconi's anemia, Gluckman et al 49 retrospectively analyzed results of unrelated CBT in 93 Fanconi anemia patients. In that series, HLA mismatches were associated with poorer survival.…”
Section: Selection Of Unrelated Donor Cb For Transplantation: Effect mentioning
confidence: 99%
“…OS was 40 ± 5% and factors associated with favorable outcome were use of fludarabine in the conditioning regimen, number of nucleated cells infused X4.9 Â 10 7 /kg, and negative CMV serology in the recipient. 2 Regarding results of UCBT in patients with acquired SAA, we have reported an analysis on 71 patients (33 males) diagnosed with SAA, (9 with PNH) who received a single UCBT (n ¼ 57, 79%) or double UCBT (n ¼ 14, 19%) between January 1996 and January 2009 in 32 centers (23 EBMT centers). 9 The median age was 13 years (range 2-68 years; 28 adults).…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%